Profil Penggunaan Antibiotik pada Balita Penderita ISPA di Puskesmas Koya Barat Periode Januari-Desember 2020 - Gunawan, Elsye; Rusnaeni, Rusnaeni; Febrianty, Silva Dewi (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: Acute Respiratory Tract Infection (ARTI) is the most common infection in humans at all ages. Children and toddlers are the most susceptible to ARTI. Prevalence of ARTI among toddler in Papua is 11.91%, in Jayapura district (10.23%) and Jayapura City (10.95%). This study aimed to determine the profile of antibiotics usage that given to toddler patients with ARTI on January-December 2020 at Koya Barat Public Health Center. The study design was retrospective of 155 prescriptions for toddler patients with ARTI that qualified the inclusion criteria. Data were analyzed using Microsoft excel software and presented in percentages (%) based on patient characteristics, and the level of antibiotic use was calculated. The results showed that male toddler was dominantly affected by ARTI, namely 87 patients (56,13%), age 0-30 months were 87 patients (56,13%), the type of antibiotic amoxicillin syrup used were 57 patients (74,03%). Overall used of antibiotics in toddler with ARTI at Koya Barat Public Health Center during January-December 2020 was 49,68%. Toddler with ARTI without comorbidities were 86,59%, and with comorbidities such as diarrhea, malaria, blepharitis, and pyoderma were 13.41%.